Indonesia and the Muslim world Islam and secularism in the foreign policy of Soeharto and beyond - Perwita, Anak Agung Banyu (NIAS reports ;, 2007)
Exploring Islam as a domestic political variable in Indonesia's foreign policy, this book argues that the foreign policy toward the Muslim world was based on domestic political struggles between local actors, particularly the Muslim community and the State. It includes a chapters covering Indonesia's policy toward the war in Bosnia-Herzegovina.